Bicentenary, a new potato cultivar for processing in Peru: perspectives from plant breeding - Contreras, Sergio (2023)
The industrialization of potatoes in Peru constitutes a business opportunity to increase the supply of processed potatoes, generating added value for small producers. For this reason, it is important to have varieties suitable for frying and thus supply the potato value chain for the processing industry (french fries) and snacks (flakes). It is described the origin and genealogy of the clone UH-24 (“Bicentenaria”), its agronomic characteristics through the identification analysis, the way how it developed and multiplied in the greenhouse and in the field, as well as the evaluation process through the analysis of adaptation and efficiency in four environments of Lima region. The potato variety Bicentenaria has good production and adaptation capacity in the central coast of Peru, with a mean tuber yield of 43.2 t ha-1, compared to the commercial varieties Canchán and Diacol Capiro with 37.22 and 32.5 respectively and higher than the clone UH-18 with 31.6 t ha-1. It is concluded that “Bicentenaria” is a potato cultivar with high yields, good phenotypic stability and attributes such as soluble solids and type of tuber suitable for processing as french fries and chips.